The influence of polyphenolics on the nutritive value of browse: A summary of research conducted at ILCA - Woodward, A.; Reed, J.D. (1989)
Summarises ILCA's findings over several years of research on the nutritive value of browse plants. Discusses nitrogen metabolism in ruminants and tannin chemistry. Examines the effect of browse on animals, i.e., feed intake, growth, digestion of fibre fractions and utilisation of nitrogen. Discusses factors affecting the use of browse. Presents data on the contents of soluble phenolics and insoluble proanthocyanidins, browse and roughage intakes and growth rate in sheep, digestibility of organic matter, neutral detergent fibre & acid-detergent lignin for sheep. Also examines digestibility of dry matter, rumen ammonia and plasma urea nitrogen concentrations and daily urinary nitrogen loss, and nitrogen digestibility and contents of soluble phenolics and insoluble proanthocyanidines.